School Grouping and Students' Goal Achievement in Universities in Kwara State, Nigeria - Adeseko Sunday Olaifa; Meimuna Mohammed; Monsurat Iyabo Alao; , Hafiz Babajide Ibrahim; Oba Baba Ayoku (Eduvis : Jurnal Manajemen Pendidikan Islam, 2024)
School group dynamics are critical factors influencing students' educational experiences and outcomes. This study investigated the relationship between school group dynamics and students' goal achievement in Universities in Kwara State, Nigeria. The study was guided by two research questions and five research hypotheses. The descriptive survey of the correlational type was adopted for the study. The population of this study comprised 77,984 undergraduates. A sample of 385 undergraduates was selected using purposive and simple random sampling techniques. A researcher-designed instrument titled School Group Dynamic and Students' Goal Achievement Questionnaire (SGDSGAQ) was utilised for data collection. A reliability test was conducted, yielding coefficient values of 0.89. Mean ratings were used to answer the research questions, while Pearson product-moment correlation statistic was employed to test the hypotheses at a 0.05 significance level. The findings of this study showed that school groups in Kwara State Universities are highly available, including social groups, academic groups, political groups, and cultural groups. Similarly, the study showed that students’ achievement goals in universities at Kwara State are high. The study also revealed a significant relationship between school group dynamics and students' goal achievement in Universities in Kwara State. It was recommended that universities enhance the organisation and visibility of these groups by establishing a formal framework for group registration, participation, and leadership. Universities should encourage multidisciplinary collaborations across different types of groups (social, educational, political, and cultural).